Prevalence of diabetes distress and its psychosocial determinants among Indian population with type II diabetes - Purushottaman, Suraj; Joshi, Ameya; Dalal, Dhaval; Fahaad, Mohd; Rao, Namrata; Gore, Shivanjali; Vijay, Ria (International Journal of Research in Medical Sciences, 2024)
Background: Diabetes distress (DD) refers to the negative emotional or affective experience resulting from the challenge of living with the demands of diabetes, regardless of the type of diabetes. In addition to the chronic treatment of diabetes, patients with type 2 diabetes mellitus (T2DM) often experience psychosocial difficulties which can go unnoticed. Hence, it is necessary to identify DD at an early stage to prevent its effect on the patients’ long-term self-care and management plan. This study was conducted to assess the prevalence of DD and its psychosocial determinants among T2DM at a tertiary care centre. Methods: This was a cross sectional, observational study which included patients of either gender, who were between 18-65 years of age with T2DM for more than 3 months to 12 years. DD was assessed using the diabetes distress scale (DDS17) scale. In addition, association between the level of DD with the sociodemographic and clinical characteristics of the patients was assessed. Results: The prevalence of DD in type II diabetic patients in suburban population was found to be 17.69%. The psychosocial determinants which influence DD were found to be age, treatment modality, hypothyroidism, hypertension, and smoking. Conclusions: This study signifies the importance of identifying DD by the primary care physician which often remain unrecognized in clinical practice and to implement the interventions at early stages to improve the quality of life of diabetic patients.